Implementasi Kepemimpinan Spiritual Kepala Madrasah dan Budaya Religius dalam Membentuk Kinerja Guru di MI Roudlotul Hikmah Mojokerto - Muhammad Ibnu Alwan Khoirul; Eka Rizki Amalia (Educational Journal, 2026)
Teacher performance is one of the main factors in improving the quality of Islamic education in madrasahs. However, challenges in developing teacher professionalism require leadership that is not only administrative in nature but also spiritual and supported by a strong religious culture. This study is important to examine the implementation of the spiritual leadership of the madrasah principal and religious culture in shaping teacher performance at MI Roudlotul Hikmah Mojokerto. The purpose of this study is to describe the implementation of the principal’s spiritual leadership, the application of religious culture, and their impact on teacher performance. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the madrasah principal, teachers, and educational staff. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was tested through source and technique triangulation. The findings revealed that the implementation of spiritual leadership was manifested through exemplary behavior, Islamic motivation, spiritual guidance, and humanistic communication. Religious culture was implemented through habituation of worship activities, collective prayers, and the culture of greetings and politeness. The implementation had a positive impact on improving teachers’ discipline, responsibility, professionalism, and work ethic. Therefore, spiritual leadership and religious culture are important foundations for strengthening the quality of Islamic education in madrasahs.